Suitable Models for Describing Sulphate Desorption Kinetics in Selected Bauchi North Soils of Varying Parent Materials in the Nigerian Sudan Savanna - Murabbi Aliyu; M. Abdulkadir; I.M. Azare; N. Abdu; I. S. Nuhu; A. I. Saminu (Universitas Panji Sakti, 2022)
The modelling of sulphate desorption data is critical for a proper S diagnosis and fertilizer formulation to ensure profitable crop production. Five (5) models such as first-order, second-order, Elovich, fractional power, and parabolic diffusion were used to test the best model describing sulphate desorption kinetics in some soils from Bauchi-north, Sudan Savanna, Nigeria. To achieve this, soil samples were collected from three different parent materials namely Basement complex rock and two sedimentary rocks (Kerri-Kerri Formation and Chad Formation). The study showed that the parabolic diffusion and first-order models were found to describe S desorption data satisfactorily, characterized by relatively high R2 values and lowest S.E values by soil parent materials, respectively. While, the second-order, Elovich and Fractional power equations failed to describe the kinetics desorption of sulphate in all the studied soils, as judged by their high SE values. Therefore, the better fit of S desorption data to the first-order equation is an indication of probable ligand exchange of sulphate ion during the desorption process, and to parabolic diffusion equation suggests that diffusion-controlled phenomena are rate-limiting steps. Based on the findings, we concluded that the rate of sulphate desorption kinetics in these soils is mainly controlled by diffusion-controlled phenomena, which is critical for sulphate-based fertilizer formulations and applications.